Microfluidic preparation of size- and lamellarity-controlled liposomes using a static mixer and the advantage of a multilamellar structure in biosensing applications - Kiuchi, Makoto; Takeoka, Shinji; Sou, Keitaro (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundLiposomes are useful tools for amplifying signals in biosensing techniques, which are used to detect and analyze biological molecules. The goal of this study is to improve the sensitivity of immunosorbent assays by optimizing the self-assembled structure of lipids in temperature-responsive liposomes that carry lipophilic fluorescent dyes as a detection probe in their bilayer membrane. We hypothesized that increasing the number of bilayer membranes (lamellarity) in liposomes would enhance the fluorescence signal and improve assay sensitivity, as liposomes with larger lamellarity would have a larger membrane capacity to carry the fluorescent dye per liposome of the same size.MethodsBased on this hypothesis, we first examined the microflow mixing of a lipid-ethanol solution with an aqueous medium using a static mixer to determine the optimal conditions for controlling liposomal size and lamellarity. We applied the resulting multilamellar liposomes, of which surface was modified with antibodies, as a detection probe in an immunosorbent assay for prostate-specific antigen (PSA).ResultsIn-line mixing with a static mixer generates liposomes of a controlled size and lamellar structure, depending on the lipid concentration, mixing ratio, and flow velocity. Notably, the initial lipid concentration in ethanol significantly impacts the lamellarity of the liposomes at a low flow velocity. The results of the immunosorbent assay using the liposomal probe indicated that a greater number of bilayer membranes produces a stronger fluorescent signal, enabling more sensitive detection of PSA.ConclusionStatic mixer-based microfluidics enables the preparation of size- and lamellarity-controlled liposomes by adjusting the processing conditions. This structural control could improve the performance of liposomes in various applications, including biosensing.